Laparoscopic and laparotomic guided ureteral stenting during gynecological surgery without use of imaging: Safety and feasibility in a single institutional case series. (August 2020) - Romano, Federico; Rizzo, Michele; Stabile, Guglielmo; Di Lorenzo, Giovanni; Liguori, Giovanni; Trombetta, Carlo; Ricci, Giuseppe
Abstract: Objectives: Aim of this study is to refer a single center experience of laparoscopic or laparotomic assisted ureteral stenting without the use of imaging guidance. Study design: We recruited 19 patients in the Institute for Maternal and Child Health in Trieste (Italy) who underwent ureteral stenting between June 2017 and December 2018 for suspicious ureteral injury during gynecological surgery. Ureteral stents insertions were performed in all cases using rigid cystoscopes, hybrid guidewire with a hydrophilic coating, and double loop ureteral stents; the ureters were skeletonized during surgery and stents were used to permit better visualization of the ureteral whole and to prevent complications connected with the ureteral devascularization and minor not recognized ureteral injuries. All the procedures were performed under a laparoscopic or laparotomic guide. Results: No sign of acute kidney failure was reported during the post-operative kidney functions evaluation. The right position of the stents was confirmed in the first postoperative day by ultrasonographic imaging. No major complications related to the urinary tract have been detected. Ten patients stated stent related symptoms well controlled by analgesic therapies. All stents were removed by office cystoscopies one month later without reporting any complication. Conclusions: Introducing fluoroscopy or ultrasonographic imaging into the operative field could be difficult and time-consuming. Instead, the laparoscopic and laparotomic guided ureteral stenting without the use of imaging currently used in the standard clinical practice of many institutions even without an official standardization in order to treat or prevent ureteral injuries after the surgery, seems to be safe and feasible.